Evaluation of the effectiveness of an anti-vibration MTB handlebar compared to a traditional MTB handlebar - Perrotin, N.; Duc, S.; Puel, F.; Bertucci, W. (Journal of Science and Cycling, 2019)
Background: Exposure to mechanical vibration during road cycling is a potential risk factor for injuries or musculoskeletal disorders such as the ulnar tunnel syndrome (Akuthota et al., 2005:The American Journal of Sports Medicine, 33, 1224-1230)that results in impaired handgrip force, reduced mobility and pain in both the hands and arms (Radwin et al., 1987: Ergonomics, 30, 833-855).Over the last decade, bike manufacturers have designed anti-vibration components to prevent such symptoms. A recent study showed that new ergonomic MTB grips could prevent fatigue by reducing both vibrations and muscular activity in the forearm while preserving maximal handgrip force(Scholler et al., 2018: Journal of Science & Cycling, 7).